Other ever afters new queer fairy tales - Gillman, Melanie (Random House Graphic, 2022)
In this new feminist, queer fairy tale collection, the princesses, mermaids, barmaids, children, and wise old women who have been forced to sit on the sidelines in classic stories take center stage to fulfill their own dreams and find the love, power, and happiness they deserve